Attitudes and Perceptions Toward Healthcare Technology Adoption Among Older Adults in Singapore: A Qualitative Study - Sarah T. H. Low; P. Govind Sakhardande; Yi Feng Lai; Yi Feng Lai; Yi Feng Lai; Andrew D. S. Long; Satveer Kaur-Gill (Frontiers Media S.A., 2021)
Smart Nation is a key initiative of Singapore to move toward digitalization of its industries including healthcare. The complex negotiations of aging amid Smart Nation are addressed in this paper, where we study the challenges faced to adapt the elderly for the digital revolution while ensuring dignified aging. While the healthcare industry accelerates its study and use of health technologies to improve diagnostics, treatment, and the quality of life of those in the aging category, the elderly socially construct these technological insertions that challenge the dominant understandings of what these technologies can do for their health outcomes. The study reveals re-constructions of these technological insertions through the voice of the elderly in their negotiations with health technologies in their everyday lives. Here, narratives reveal key themes that proliferate technology negotiation as barriers to everyday lived experiences.